FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN OPINI AUDIT GOING CONCERN - Vernando, Andreas; Yuniarto, Arif Sapta (Universitas Ahmad Dahlan, 2014)
Auditor in doing a audit is responsible to evaluate whether auditee gets problem in maintainig its existence. One of its indication is auditee gets the financial distress. Therefore, if doubting a capable auditee in maintainig its existence, Auditor commonly brings out going concern audit opinion for giving signalement to investor so that investor does not make the mistake in interpretating the economic decision. The researchs with topics going-concern audit opinion have been comprehensive enough. this is seen of many variables gone into researchs model. However, researchs with topics going-concern audit opinion must be continously renewed. This is caused economy condition that is always dinamic having to research continously. This research purposed to obtain the empirical evidence of factors influencing acceptance going-concern audit opinion. This research focussed for researching manufacture sector which was listed at Indonesian stock exchange from periods 2009 until 2012 used as research sample. the result of purposive sampling method was obtained as many as 39 manufacture companies which fill up sample criterion and the tests of hypotesis use logistic regression analysis. The results of hypotesis test showed that tenure influenced acceptance of going-concern audit opinion